2019
DOI: 10.1002/jso.25613
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for anastomotic leak after esophagectomy for cancer: A NSQIP procedure‐targeted analysis

Abstract: Background: Anastomotic leak is the most common major complication after esophagectomy. We investigated the 2016 American College of Surgeons National Surgical Quality Improvement Program esophagectomy targeted database to identify risk factors for anastomotic leak.Methods: Patients who underwent esophagectomy for cancer were included. Patients experiencing an anstomotic leak were identified, and univariate and multivariable logistic regression was performed to identify variables independently associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 46 publications
(80 reference statements)
3
27
1
Order By: Relevance
“…The multivariate analysis suggested that operation time longer than 360 minutes signi cantly increased the risk of major PCs (OR 6.753, 95% CI 2.037-22.395, p = 0.002). This nding was consistent with other studies [27][28][29]. Secondly, the pathologic stage of patients enrolled in this study were much later.…”
Section: Diagnostic Accuracy and Optimal Cut-off Value Of Each Markersupporting
confidence: 93%
“…The multivariate analysis suggested that operation time longer than 360 minutes signi cantly increased the risk of major PCs (OR 6.753, 95% CI 2.037-22.395, p = 0.002). This nding was consistent with other studies [27][28][29]. Secondly, the pathologic stage of patients enrolled in this study were much later.…”
Section: Diagnostic Accuracy and Optimal Cut-off Value Of Each Markersupporting
confidence: 93%
“…Univariate and multivariate analyses of clinical factors for major postoperative complicationsThe multivariate analysis suggested that operation time longer than 360 minutes signi cantly increased the risk of major PCs (OR 6.753, 95% CI 2.037-22.395, p=0.002). This nding was consistent with other studies[23][24][25]. Furthermore, our research revealed that proximal gastrectomy with double-tract anastomosis increased the risk of major PCs (OR 8.224, 95% CI 1.976-34.234, p=0.004).…”
supporting
confidence: 93%
“…Moyes et al reported that elevated preoperative white cell count ( P <0.05) were independently associated with increased risk of developing a postoperative infection [ 31 ]. Another recent study showed that increased preoperative WBC count was independently associated with anastomotic leak after esophagectomy [ 32 ]. In aforementioned analysis, the authors estimate that for every 3000/μL increase in the preoperative WBC count, the associated risk increased by 32% [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study showed that increased preoperative WBC count was independently associated with anastomotic leak after esophagectomy [ 32 ]. In aforementioned analysis, the authors estimate that for every 3000/μL increase in the preoperative WBC count, the associated risk increased by 32% [ 32 ].…”
Section: Discussionmentioning
confidence: 99%